(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The main global trends of the organization of executive on-boarding process (its legal status, participants, character of the results of the on-boarding process, labor turnover indicators for executives) are analyzed in the article. The key distinctive features between executive on-boarding and on-boarding of lower personnel are revealed; in particular main participants of the process of executive on-boarding, their typical charge or scope of responsibility are defined. The connection between level of the managerial position and individualization of approach to on-boarding in global leading companies is highlighted. Set of recommendations aimed on development of modern executive on-boarding program is elaborated. The main goals of the human resources department in the process of executive on-boarding are developed. An exceptional role of the executive on-boarding is described both from the perspective of the outcomes of enterprise, as well as moral and psychological conditions of staff and image of an enterprise in general